Добрый доктор Айбандит: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2013)
Экземпляры: ф.12 (20220321) / Инвентарный номер: 63485 / Цена: 30.00 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44